A review of object-oriented approach for test case prioritization - Umar Farooq; Hannani Aman; Aida Mustapha; Zainuri Saringat (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The most essential phase in regression testing is Test Case Prioritization (TCP), with its primary objective to increase the fault detection rate at different stages during testing. Prior to achieving the objective, existing evidence of techniques in TCP must be synthesized and analyzed. At present, fault detection for TCP based on object-oriented features only consider statement, module, and class level. The important features of object-oriented (OO) programming like inheritance and polymorphism have not been fully explored for fault detection in TCP. Such OO concepts are important for test case selection and in turn for ranking the test cases (prioritization). This paper reviews various test case prioritization techniques specific to OO systems. This review is hoped to highlight the importance and usage of TCP in relation to object-oriented software development lifecycle.